Louisiana fiddlers - Yule, Ron (American made music series., 2009)
Louisiana Fiddlers shines light on sixty-two of the bayou state's most accomplished fiddlers of the twentieth century. Author Ron Yule outlines the lives and times of these performers, who represent a multitude of fiddling styles including Cajun, country, western swing, zydeco, bluegrass, Irish, contest fiddling, and blues. Featuring over 150 photographs, this volume provides insight into the "fiddlin' grounds" of Louisiana. Yule chronicles the musicians' varied appearances from the stage of the Louisiana Hayride, honky tonks, dancehalls, house dances, radio and television, and festiv